Bone Marrow Stimulation and Biologics for Osteochondral Lesion of the Talus: A Systematic Review and Meta-Analysis of Clinical Comparative Studies. Issue 4 (November 2022) - Ubillus, Hugo A.; Seow, Dexter; Azam, Mohammad T.; Yasui, Youichi; Mercer, Nathaniel P.; Weiss, Matthew B.; Pearce, Christopher J.; Kennedy, John G.
Category: Ankle; Ankle Arthritis; Basic Sciences/Biologics; Sports; Trauma Introduction/Purpose: Osteochondral lesion of the talus (OLT) is a commonly occurring injury, typically treated with bone marrow stimulation (BMS) in the small to medium-sized lesions after a failed course of conservative treatment. The current evidence suggests that biologics can improve chondrocyte growth and differentiation. However, the lack of consensus to date on the efficacy of biologics + BMS for OLT has warranted further investigation. The purpose of this study is to clarify the effectiveness and safety of biologics as an augmentation in BMS by assessing complication rates, continuous functional outcome scores and return to play data compared to BMS alone for OLT. Methods: A systematic review and meta-analysis were performed. The PubMed and Embase databases were searched using specific search terms and eligibility criteria according to the PRISMA guidelines. The level of evidence was assessed using published criteria by The Journal of Bone & Joint Surgery and the quality of evidence using the Modified Coleman Methodology Score. Fixed- effects models were employed if heterogeneity was graded low (I2 <25%), and random-effects models if heterogeneity was graded moderate to high (I2>=25%). Results: For BMS versus BMS + hyaluronic acid (HA), the fixed-effects model for American Orthopaedic Foot and Ankle Society score revealed a mean difference increase that is an improvement of 4.88 (95% CI, 2.33 to 7.44; I2 = 0%; p = 0.0002) points, in favor of BMS + HA. The fixed-effects model for 10mm Visual Analog Scale pain revealed a mean difference decrease that is an improvement of 1.21 (95% CI, 0.70 to 1.73; I2 = 0%; p < 0.00001) points, also in favor of BMS + HA. For BMS versus BMS + concentrated bone marrow aspirate (CBMA), the pooled complication rate was 17/64 (26.6%) versus 11/71 (15.5%), respectively, with a chi-squared test of p = 0.11. The pool revision rate was 15/64 (23.4%) versus 6/71 (8.5%), respectively, with a chi-squared test of p = 0.016. Conclusion: Adjuvant biologic use with BMS may provide superior outcomes, notably that of HA and CBMA, based on the current evidence. Future studies must aim to establish the clinical superiority of the various other biologics + BMS versus BMS alone. These studies must compare the various biologics against one another to determine, if any, the optimal biologic for OLT.